Predictors of in-hospital appendiceal perforation in patients with non- perforated acute appendicitis with appendicolithiasis at presentation - Amir H. Sohail; Hazim Hakmi; Koral Cohen; Joshua C. Hurwitz; Jasmine Brite; Sawyer Cimaroli; Harry Tsou; Michael Khalife; James Maurer; Matthew Symer (BMC Surgery, 2023)
Abstract Introduction Appendicolithiasis is a risk factor for perforated acute appendicitis. There is limited inpatient data on predictors of progression in appendicolithiasis-associated non-perforated acute appendicitis. Methods We identified adults presenting with appendicolithiasis-associated non-perforated acute appendicitis (on computed tomography) who underwent appendectomy. Logistic regression was used to investigate predictors of in-hospital perforation (on histopathology). Results 296 patients with appendicolithiasis-associated non-perforated acute appendicitis were identified; 48 (16.2%) had perforation on histopathology. Mean (standard deviation [SD]) age was 39 (14.9) years. The mean (SD) length of stay (LOS) was 1.5 (1.8) days. LOS was significantly longer with perforated (mean [SD]: 3.0 [3.1] days) vs. non-perforated (mean [SD]: 1.2 [1.2] days) appendicitis (p < 0.001). On multivariate analysis, in-hospital perforation was associated with age > 65 years (OR 5.4, 95% CI: 1.4- 22.2; p = 0.015), BMI > 30 kg/m2 (OR 3.5, 95% CI: 1.3–8.9; p = 0.011), hyponatremia (OR 3.6, 95% CI: 1.3–9.8; p = 0.012). There was no significant association with age 25–65 years, gender, race, steroids, time-to- surgery, neutrophil percentage, or leukocyte count. Conclusion Geriatric age, obesity, and hyponatremia are associated with progression to perforation in appendicolithiasis-associated non-perforated acute appendicitis.